The Jurisprudential Preferences of Imam Ibn Ruslan in His Commentary on Sunan Abi Dawud Regarding Certain Rulings on Friday Prayer: A Comparative Study - Alaa Abd Ahmed Khalaf,; Muhammad Amin Khalaf, (Islamic Sciences Journal, 2026)
This research explores selected jurisprudential preferences regarding the rulings of Friday Prayer according to the perspective of Imam Ibn Raslan—may Allah have mercy on him—as presented in his commentary on Sunan Abi Dawud. The study consists of an introduction followed by three main sections, each divided into two subtopics: Section One is dedicated to introducing Imam Ibn Raslan. The first subtopic discusses his personal life, while the second addresses his birth, upbringing, place of residence, and death. Section Two focuses on the biography of Imam Abu Dawud. The first subtopic covers his personal life, and the second explores his scholarly journeys and his passing. Section Three discusses certain jurisprudential rulings related to the Friday Prayer. The first subtopic examines the ruling on the dialogue between the preacher and the listener during the sermon, while the second investigates the ruling concerning a latecomer who does not catch at least one rak‘ah with the imam. The research concludes with a summary of the key findings, followed by a list of sources and references..